PENGUJIAN KETAHANAN BILAH BAMBU PETUNG (Dendrocalamus asper (Schults f.) Backer ex Heyne) TERHADAP JAMUR DENGAN CARA HAMPARAN TANAH - Krisdianto (BRIN Publishing, 2012)
Durability performance is one of the important aspect of bamboo basic properties. As a lignocellulose material bamboo is susceptible to degrade by various organisms including fungi. Durability of bamboo is commonly assessed using wood laboratory testing procedure, such as agar plate method, an alternative soil bed test using unsterile soil is one attractive durability test method as it is cheap and simple to set up. This paper studies bamboo strips durability against fungus using soil bed test method. Bamboo strip tested were taken radially from inner (i), middle (m) and outer (o), and also longitudinally from bottom (B), parts of Dendrocalamus asper culms. The results show inner part strip (i) is more susceptible to fungi than the middle (m) and outer part (o). Almost all bamboo strips taken from inner part (1) failed to pin and hand bending test after six months exposure. Samples exposed in soil bed with 100% water bolding capacity decayed more severely than the 80% water bolding capacity. The bamboo strips from bottom (B) part were less susceptible than middle (M) and top (T) of bamboo height, bowever, the difference was not significant. Soil bed is an effective test method for bamboo strips durability against fungi.